Вплив зеленого кольору на сприйняття бренду - Шабуня, Д. Є. (ХНУРЕ, 2025)
This paper explores the impact of green color on brand perception and consumer behavior. Green is commonly associated with nature, safety, and reliability, making it a widely used color in environmental, financial, and healthcare branding. The study highlights the psychological effects of green, its application across various industries, and its role in shaping consumer trust. Additionally, the paper examines the ethnocultural differences in green color perception and their influence on international branding strategies.
Keywords: вплив зеленого кольору; сприйняття бренду